Impairment in Theory of Mind in Parkinson's Disease Is Explained by Deficits in Inhibition. (28th May 2019) - Foley, Jennifer A.; Lancaster, Claire; Poznyak, Elena; Borejko, Olga; Niven, Elaine; Foltynie, Thomas; Abrahams, Sharon; Cipolotti, Lisa
Abstract : Objective . Several studies have reported that people with Parkinson's disease (PD) perform poorly on tests of 'Theory of Mind' (ToM), suggesting impairment in the ability to understand and infer other people's thoughts and feelings. However, few studies have sought to separate the processes involved in social reasoning from those involved in managing the inhibitory demands on these tests. In this study, we investigated the contribution of inhibition to ToM performance in PD. Methods . 18 PD patients and 22 age-matched healthy controls performed a ToM test that separates the ability to infer someone else's perspective from the ability to inhibit one's own. Participants also completed a battery of standard measures of social and executive functioning, including measures of inhibition. Results . The PD patients performed worse on the ToM test only when the inhibitory demands were high. When the level of inhibition required was reduced, there were no significant group differences. Furthermore, executive impairments in PD patients were limited to measures of inhibition, with disadvantages associated with poorer ToM performance in this group. Conclusions . This study provides convincing evidence that the apparent impairment observed on ToM tests in PD is explained by deficits in inhibition.